2003
DOI: 10.1093/hmg/ddg017
|View full text |Cite
|
Sign up to set email alerts
|

Human BOULE gene rescues meiotic defects in infertile flies

Abstract: Defects in human germ cell development are common and yet little is known of genes required for germ cell development in men and women. The pathways that develop germ cells appear to be conserved broadly, at least in outline, in organisms as diverse as flies and humans beginning with allocation of cells to the germ cell lineage, migration of these cells to the fetal gonad, mitotic proliferation and meiosis of the germ cells, and maturation into sperm and eggs. In model organisms, a few thousand genes may be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 29 publications
4
93
0
2
Order By: Relevance
“…For example, insertion of human DAZ or DAZL transgenes into DazlKO mice can increase the numbers of germ cells (Slee et al, 1999;Vogel et al, 2002) but is not able to restore fertility. Meiotic defects in Boule mutant Drosophila can be rescued by the Xdazl gene from frogs (Houston et al, 1998) and by a human BOULE transgene (Xu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, insertion of human DAZ or DAZL transgenes into DazlKO mice can increase the numbers of germ cells (Slee et al, 1999;Vogel et al, 2002) but is not able to restore fertility. Meiotic defects in Boule mutant Drosophila can be rescued by the Xdazl gene from frogs (Houston et al, 1998) and by a human BOULE transgene (Xu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The DAZL/DAZ genes evolved after a series of gene duplications from Email: p.saunders@ed.ac.uk the ancestral Boule gene first identified in the fly (Xu et al, 2001). Although sequence divergence between Boule genes in flies and humans is low (Xu et al, 2003), DAZ and DAZL homologues have diverged rapidly in primates (Bielawski and Yang, 2001). Immunoexpression studies on sections from rodent and human testes using antibodies specific for DAZ, DAZL or BOULE have shown that all are expressed exclusively in the germline lineage although their patterns of expression are distinct (Xu et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Human BOULE can rescue partial testicular defects of fruit flies with boule mutant (Xu et al 2003). Furthermore, frog dazl can restore fly boule mutant to some extent, though frog dazl show a germline function different from fly boule (Houston et al 1998;Houston and King 2000).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The expression of DAZ family genes is specific to germ cells [12]. In addition, the role of the DAZ family on germline development appears to be conserved across species from invertebrates to mammals, which is evident by the finding that human Dazl can partially rescue the Drosophila boule mutant [13]. Disruption of the Dazl gene in mice results in a loss of germ cells and complete absence of gametes in the female, and a failure to differentiate past meiotic prophase I during spermatogenesis [8,14].…”
Section: Introductionmentioning
confidence: 99%